Limited genetic variability in Megasphaera elsdenii strains - Piknová, M; Bíres, O; Javorský, P; Pristas, P (Folia microbiologica, 2006)
Levels of phenotypic and genotypic diversity among seven Megasphaera elsdenii strains recovered from rumen contents of cattle, sheep and lambs were determined by a combination of antibiotic-resistance analysis and PCR fingerprint techniques targeted both to the ribosomal RNA operon (ARDRA, RISA) and the whole genome (ERIC-PCR, RAPD-PCR). Despite exhibiting different antibiotic resistance profiles, the tested strains represent genetically nearly identical isolates. Close genetic relatedness was found among M. elsdenii isolates that originated from vastly different habitats worldwide, as revealed by the comparison of 16S rDNA sequences.
Keywords: genotyp; Animals; molekulární sekvence - údaje; skot; Phenotype; DNA bakterií; DNA, Bacterial; Molecular Sequence Data; ovce; RNA ribozomální 16S; genetická variace; bachor; DNA fingerprinting; RNA, Ribosomal, 16S; Microbial Sensitivity Tests; Rumen; zvířata; fylogeneze; Megasphaera; Cattle; mikrobiální testy citlivosti; Sheep; Phylogeny; fenotyp; Genotype; DNA Fingerprinting; Genetic Variation